Object-Oriented programming in java - Stephen Gilbert (Mitchell waite, 1997)
What's this java stuff; Programs: the community of objects; The atomic theory of objects: working with; Simply methods: one step at a time; Making choices: teaching your objects about true and false; Teaching your objects to repeat themselves...